Specific health beliefs mediate sex differences in food choice - Egele, Viktoria S.; Stark, Robin (Frontiers in Nutrition, 2023)
Objective: Although sex differences in dietary habits are well documented, the etiology of those differences is still a focus of research. The present study examines the role of specific health beliefs regarding healthy amounts of food for food choice and its relation to sex, more specifically, the assumption that sex differences in food choices are mediated by differentiating health beliefs. Method: 212 German participants (44.3% female) aged 18 - 70 answered an online self-report questionnaire on their dietary habits and health beliefs, based on the recommendations of the German Nutrition Society. Results: Most of the anticipated sex differences in food choice and some differences in health beliefs were found. The mediation hypothesis was partly supported, as the relationship between sex and fruit, vegetable, and fish consumption was mediated by the respective health beliefs. However, no mediation effects were found for meat, egg, cereal, and milk product consumption. Conclusion: The support for the mediation hypothesis aligns with previous findings and indicates that health beliefs might be an important pathway to fostering healthier food choices, especially for men. Nonetheless, sex differences in food choice were only partially mediated by sex differences in specific health beliefs, indicating that future studies might benefit from parallel mediation analyses to reveal the impact of other relevant factors influencing sex differences in food choice.